2017
DOI: 10.1111/joic.12479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors associated with physician choice of femoral versus radial access: A real‐world experience from a single academic center

Abstract: STEMI or emergent cases and elderly patients favor upfront femoral access. As BMI increases and age decreases, radial access is progressively favored. In diagnostic cases, radial access appears to be superior to femoral access in efficacy, but the distinction is less obvious in PCI and STEMI or emergent cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The same occurs in the elderly population, which also tends to benefit more from radial access due to a lower incidence of bleeding (Yee, 2018;Walter, 2017).…”
Section: Risk Factors For Post-withdrawal Complicationsmentioning
confidence: 89%
“…The same occurs in the elderly population, which also tends to benefit more from radial access due to a lower incidence of bleeding (Yee, 2018;Walter, 2017).…”
Section: Risk Factors For Post-withdrawal Complicationsmentioning
confidence: 89%
“…Yee et. al concluded that trans-radial access is progressively preferred as BMI increases and in younger patients, while in STEMI or emergent cases and elderly patient trans-femoral access is preferred (18).…”
Section: Discussionmentioning
confidence: 99%